2014
DOI: 10.1186/1476-069x-13-94
|View full text |Cite
|
Sign up to set email alerts
|

Short-term airborne particulate matter exposure alters the epigenetic landscape of human genes associated with the mitogen-activated protein kinase network: a cross-sectional study

Abstract: BackgroundExposure to air particulate matter is known to elevate blood biomarkers of inflammation and to increase cardiopulmonary morbidity and mortality. Major components of airborne particulate matter typically include black carbon from traffic and sulfates from coal-burning power plants. DNA methylation is thought to be sensitive to these environmental toxins and possibly mediate environmental effects on clinical outcomes via regulation of gene networks. The underlying mechanisms may include epigenetic modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 76 publications
0
46
0
1
Order By: Relevance
“…Evidence also suggests effects on methylation specific to airway inflammation: nitric oxide synthase 2a methylation decreased within 24 hours of PM 2.5 exposure (22). Reduced methylation of inflammation genes.was also associated with acute or intermediate-term exposure to air pollutants (19,(21)(22)(23)(24)50).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Evidence also suggests effects on methylation specific to airway inflammation: nitric oxide synthase 2a methylation decreased within 24 hours of PM 2.5 exposure (22). Reduced methylation of inflammation genes.was also associated with acute or intermediate-term exposure to air pollutants (19,(21)(22)(23)(24)50).…”
Section: Discussionmentioning
confidence: 97%
“…In considering biological pathways by which PM 2.5 could induce inflammation, DNA methylation at sites regulating gene expression could play an important role (18,19). Several recent studies have reported PM 2.5 -related reductions in DNA methylation in noncoding repetitive elements, including long interspersed nuclear element-1 (20) and Alu (21), a short interspersed nuclear element, both of which are considered surrogates for global methylation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…54 We have also reported that particulate air pollution was associated with changes in methylation in the MAPK pathway within the NAS cohort, but were unable to analyze metal components as in this study. 55 Earlier, we found that particles from oil combustion were associated with markers of inflammation and endothelial dysfunction, and with increased blood pressure in the NAS population. 56,57 The current study may indicate potential mechanisms of PM-related health effects on an epigenetic level: specifically, a proinflammatory stimulus such as air pollution may modify methylation in genes relevant to immune responses, inducing inflammation and endothelial dysfunction, thereby influencing cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is possible to deconvolute these lineages, it is logistically difficult in limited samples and resource intensive. Another possibility for blood-based study is to directly measure the cell count in the DNA sample [36,37] and determine how much of the methylation signal is co-linear with the cell counts. However, such measures are not always feasible, for instance, when studying previously frozen samples, or solid tissues that are not easily fractionated.…”
Section: Partitioning the Relative Contributions Of Cellular MIX And Chmentioning
confidence: 99%